2016
DOI: 10.1002/jgm.2878
|View full text |Cite
|
Sign up to set email alerts
|

Anguilla japonica lectin 1 delivery through adenovirus vector induces apoptotic cancer cell death through interaction with PRMT5

Abstract: The results of the present study suggest that the PRMT5-E2F-1 pathway may act as a common target for exogenous lectins including AJL1, and the cellular response to exogenous AJL1 may suggest a novel agent for cancer gene therapy. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
1
16
1
Order By: Relevance
“…Our results showed that Ad-UPL1 dramatically stimulated the phosphorylation of ERK1/2 in both BEL-7404 and Huh7 cells, different from previously reported exogenous AJL1, which completely inhibited ERK1/2 phosphorylation [14]. In the meanwhile, we further showed that MEK1/2 inhibition significantly enhanced the Ad-UPL1 induced cytotoxicity.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Our results showed that Ad-UPL1 dramatically stimulated the phosphorylation of ERK1/2 in both BEL-7404 and Huh7 cells, different from previously reported exogenous AJL1, which completely inhibited ERK1/2 phosphorylation [14]. In the meanwhile, we further showed that MEK1/2 inhibition significantly enhanced the Ad-UPL1 induced cytotoxicity.…”
Section: Discussioncontrasting
confidence: 78%
“…The varied distribution of exogenous lectins may reflect varied subcellular glycosylation patterns, thus providing binding sites for different lectins. Our studies also showed that exogenous lectins including PPA, DlFBL, SpRBL, AJL1, HddSBL [11][12][13][14] as well as UPL1 induced varied intracellular signaling pathways. Taken together, varied intracellular signaling pathways affected by Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…For example, Maackia amurensis seed lectin [1], Concanavalin A [2], Fenneropenaeus indicus hemolymph fucose binding lectin [3], Polygonatum cyrtonema lectin [4], as well as MytiLec [5,6,7] were shown to be cytotoxic to various cancer cells through inducing apoptosis or autophagy. Through adenovirus-mediated gene delivery, the mannose binding plant lectin Pinellia pedatisecta agglutinin (PPA), as well as marine lectins, such as galectin Anguilla japonica lectin 1, Haliotis discus discus sialic acid binding lectin (HddSBL), Dicentrarchus labrax fucose binding lectin (DlFBL), and Strongylocentrotus purpuratus rhamnose binding lectin, could be exogenously expressed in various cancer cells and led to cancer cell death [8,9,10,11]. PPA delivered through a CD123 retargeted oncolytic adenovirus significantly inhibited in vivo leukemic xenograft growth, suggesting a possible anticancer lectin gene therapy strategy for cancer treatment [12].…”
Section: Introductionmentioning
confidence: 99%